Rules of engagement: Strategies used to enlist and retain underserved mothers in a mental health intervention - Maureen Baker; Beth Black; Linda Beeber (The Beryl Institute, 2018)
Patient engagement has been identified as both a goal and strategy to lower health care costs and improve health care outcomes. However, a lack of consensus and clarity exists as to how the process of patient engagement is implemented in clinical practice. Research addressing the underlying and crucial components of effective patient engagement is limited, leaving a significant gap as to how providers engage patients as active collaborators in their health and health care. This study provides specific, detailed insight and description into the processes through which advanced practice mental health nurses engaged low-income depressed mothers in a mental health intervention. The Interactive Care Model (ICM), a patient engagement framework, was used to examine and illuminate the key processes and partnership roles of patient engagement. Using a directed content analysis approach, we completed a secondary analysis of nursing narrative data using the 5 key processes and 7 partnership roles of the ICM to guide our analysis. The ICM demonstrated great utility in capturing the processes through which advanced practice nurses enlisted, engaged, and retained low-income depressed mothers in the mental health intervention. Additionally, the nursing narrative data provided specific detail and description as to how the ICM's components were operationalized in practice. The ICM was validated by the nursing narrative data and provided sound organizational structure for the specific verbal and non-verbal engagement interventions nurses employed. Findings from this study can expand the knowledge base and understanding of the process of patient engagement and can help guide providers in executing behaviors that engage traditionally unengaged patients as active collaborators in their health and health care.